Developing the three-dimensional integrative model of teacher competencies (TRI-model) through a systematic review of teacher competencies for twenty-first century education - Sablić, Marija (Sodobna pedagogika, 2026)
The teaching profession in the post-professional era confronts a paradox: the expectation to preserve pedagogical tradition while facing a challenging educational future. Fundamental pedagogical and didactic competencies are no longer sufficient; an enhancement with competencies for the digital age, globalisation and ecological crisis is imperative. This study combines a theoretical-analytical approach with a systematic literature review in accordance with Preferred Reporting Items for Systematic reviews and Meta-Analyses (PRISMA) guidelines. The Web of Science, Scopus, ERIC, Google Scholar and Croatian Research Information System (CRORIS) databases were searched for the period 2014–2025 to identify contemporary competencies (n = 85) and for the period before 2014 to identify traditional competencies (n = 23), resulting in a total of 108 relevant sources. The literature review analyses existing competency models identifying pedagogical (personal, communicative, analytical, social, emotional, intercultural, developmental and problem-solving) and didactic dimensions (curricular, organisational, assessment, classroom climate and partnership with parents). The analysis identifies several key trends: the permanence of fundamental competencies alongside the need for reconceptualisation, the emergence of new competency domains (digital, AI, global, sustainability and metacognitive) and the need for integrative approaches. This study’s scientific contribution is a new three-dimensional integrative model of teacher competencies (TRI-model) that unifies the permanent core, contextual layer and reflective axis, enabling synergy between tradition and innovation through continuous reflective practice.
Keywords: didactic competencies; didaktične kompetence; integrative model; integrativni model; kompetence učiteljev; pedagogical competencies; pedagoške kompetence; reflective practice; refleksivna praksa; teacher competencies